Endomucin prevents leukocyte–endothelial cell adhesion and has a critical role under resting and inflammatory conditions - Zahr, Alisar (Nat Commun, 2016)
Endomucin is a membrane-bound glycoprotein expressed luminally by endothelial cells that line postcapillary venules, a primary site of leukocyte recruitment during inflammation. Here we show that endomucin abrogation on quiescent endothelial cells enables neutrophils to adhere firmly, via LFA-1-mediated binding to ICAM-1 constitutively expressed by endothelial cells. Moreover, TNF-α stimulation downregulates cell surface expression of endomucin concurrent with increased expression of adhesion molecules. Adenovirus-mediated expression of endomucin under inflammatory conditions prevents neutrophil adhesion in vitro and reduces the infiltration of CD45(+) and NIMP-R14(+) cells in vivo. These results indicate that endomucin prevents leukocyte contact with adhesion molecules in non-inflamed tissues and that downregulation of endomucin is critical to facilitate adhesion of leukocytes into inflamed tissues.